Constructing desire(s) and consuming taste(s) among Egypt's elite: an ethnongraphic study of The American University in Cairo's new campus - Munz, Rebecca (AUC Knowledge Fountain, 2011)
This thesis demonstrates that The American University in Cairo (AUC) is a novel configuration of neo-liberal restructuring through which we can understand new trends in food consumption and new Egyptian understandings of cosmopolitanism. This study is based on anthropological fieldwork carried out predominantly on AUC's campus as well as in greater Cairo where ethnographic data was collected through interviews and participant observation. Based on the research conducted, it was found that the Egyptian government and private corporations are modernizing Cairo's cityscape in accordance with neoliberal and high modernist ideologies through promoting the construction of new social spaces which cater to emerging elite classes in Egypt. Next, the thesis argues that AUC's administration and Delicious Inc., the company chosen to provide food services on campus, are reinforcing emerging food consumption habits and participation in a global lifestyle while perpetuating social inequalities between the different social groups that study and work on the new campus. Lastly, the study argues that the corporate project is largely successful, since corporations know (a) how to discipline people to consume certain products and (b) how to modify their offerings to facilitate the kinds of foods students consume.